2020
DOI: 10.1007/s10648-020-09527-z
|View full text |Cite
|
Sign up to set email alerts
|

Learning Foreign Language Vocabulary with Gestures and Pictures Enhances Vocabulary Memory for Several Months Post-Learning in Eight-Year-Old School Children

Abstract: The integration of gestures and pictures into pedagogy has demonstrated potential for improving adults’ learning of foreign language (L2) vocabulary. However, the relative benefits of gestures and pictures on children’s L2 vocabulary learning have not been formally evaluated. In three experiments, we investigated the effects of gesture-based and picture-based learning on 8-year-old primary school children’s acquisition of novel L2 vocabulary. In each experiment, German children were trained over 5 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 99 publications
3
53
0
2
Order By: Relevance
“…Participants who saw and imitated these gestures achieved higher memory recall rates than participants in a control group. Later studies replicated and extended these initial findings (e.g., Kelly et al, 2009;Macedonia and Knösche, 2011;de Nooijer et al, 2013de Nooijer et al, , 2014de Wit et al, 2017;Andrä et al, 2020;Sweller et al, 2020).…”
Section: Effects Of Gesture-based Enrichmentmentioning
confidence: 69%
See 3 more Smart Citations
“…Participants who saw and imitated these gestures achieved higher memory recall rates than participants in a control group. Later studies replicated and extended these initial findings (e.g., Kelly et al, 2009;Macedonia and Knösche, 2011;de Nooijer et al, 2013de Nooijer et al, , 2014de Wit et al, 2017;Andrä et al, 2020;Sweller et al, 2020).…”
Section: Effects Of Gesture-based Enrichmentmentioning
confidence: 69%
“…Overall, these results suggest that considering the interplay between learner characteristics and instructional strategies is important. In a recent study, Andrä et al (2020) demonstrated the benefit of gestures over a control condition (auditorily presented words only) on children's retention of abstract and concrete nouns in two studies. A third study solely comparing pictures and gestures (without control), however did not reveal a benefit of gestures over pictures (Andrä et al, 2020).…”
Section: Picture-based Vs Gesture-based Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, teaching strategies may be advanced by establishing links between new information and congruent sensorimotor and multisensory enrichment (cf. Andrä et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%